A novel c.2179T>C mutation blocked the intracellular transport of PHEX protein and caused X‐linked hypophosphatemic rickets in a Chinese family. Issue 8 (8th June 2020) - Li, Baowei; Wang, Xiong; Hao, Xiaodan; Liu, Yanran; Wang, Yin; Shan, Chan; Ao, Xiang; Liu, Ying; Bao, HongChu; Li, Peifeng
Abstract: Background: X‐linked hypophosphatemic rickets (XLH) is a heterogeneous genetic phosphate wasting disorder that occupies the majority of inheritable hypophosphatemic rickets (HR). XLH is caused by loss‐of‐function mutations in the phosphate‐regulating endopeptidase gene ( PHEX ) located on the X chromosome. Method: In this study, we performed whole‐exome sequencing (WES) on the proband to identify the causative gene. The mutations were analyzed by predictive online software, such as PolyPhen‐2. Plasmids containing the wild‐type (WT) and mutant cDNA of the candidate gene were transfected into HEK293, then, the expression, cellular localization, and glycosylation state of the candidate proteins were detected by western blot, immunostaining, and endoglycosidase H digestion. The expression and concentration of related factor were measured by RT‐PCR and ELISA. Results: We identified a novel missense mutation c.2179T>C in the PHEX that results in the substitution of p.Phe727Leu (F727L). This mutation was predicted to be disease‐causing by all four predictive online software. In vitro studies demonstrated that the F727L substitution hindered the intracellular trafficking of the mutant PHEX, with ~59% of mutant PHEX protein retained in the endoplasmic reticulum (ER) and only ~16% of the mutant protein localized on the cell surface. Endoglycosidase H digestion assay showed that the mutant F727L PHEX protein was not fully glycosylated. The concentration of intact FGF23 in hFOB1.19 cell culture medium collected from the mutant PHEX group was the highest (62.9 pg/ml) compared to the WT group (32.1 pg/ml) and control group (23.5 pg/ml). Conclusion: Our results confirmed that the mutant PHEX protein was lowly glycosylated and retarded within the ER, the intact FGF23 level in cell culture media caused by the mutant PHEX protein was significantly elevated compared to that of the WT group, which may explain why the single base mutation in the PHEX led to XLH syndrome in this family. Abstract : In this study, we identified a novel missense mutation c.2179T>C (p.F727L) in the PHEX from an XLH family. We demonstrated that the F727L mutation decreased the glycosylation level of PHEX protein, blocked PHEX protein transport from the ER to the plasma membrane, and reduced its activity to cleave FGF23 into inactive segments, which may explain why the single base substitution c.2179T>C led to the hypophosphatemic rickets in this Chinese family.